Damaged-self recognition in common bean (Phaseolus vulgaris) shows taxonomic specificity and triggers signaling via reactive oxygen species (ROS) - Duran-Flores, Dalia; Heil, Martin (Frontiers in Plant Science, 2014)
Plants require reliable mechanisms to detect injury. Danger signals or 'damage-associated molecular patterns' (DAMPs) are released from stressed host cells and allow injury detection independently of enemy-derived molecules. We studied the response of common bean (Phaseolus vulgaris) to the application of leaf homogenate as a source of DAMPs and measured the production of reactive oxygen species (ROS) as an early response and the secretion of extrafloral nectar (EFN) as a jasmonic acid (JA)–dependent late response. We observed a strong taxonomic signal in the response to different leaf homogenates. ROS formation and EFN secretion were highly correlated and responded most strongly to leaf homogenates produced using the same cultivar or closely related accessions, less to a distantly related cultivar of common bean or each of the two congeneric species, P. lunatus and P. coccineus, and not at all to homogenates prepared from species in different genera, not even when using other Fabaceae. Interestingly, leaf homogenates also reduced the infection by the bacterial pathogen, Pseudomonas syringae, when they were applied directly before challenging, although the same homogenates exhibited no direct in vitro inhibitory effect in the bacterium. We conclude that ROS signaling is associated to the induction of EFN secretion and that the specific blend of DAMPs that are released from damaged cells allows the plant to distinguish the 'damaged self' from the damaged 'non-self'. The very early responses of plants to DAMPs can trigger resistance to both, herbivores and pathogens, which should be adaptive because injury facilitates infection, independently of its causal reason.